Fractional CO2 Laser in Treatment of Surgical and Trumatic Scars - Al-Kayalli, Khudhair Khalaf; Khalaf, Shahad Khudhair; Motllag, Mohammad Husain (Diyala Journal of Medicine, 2019)
Background: Scars result from chronic wound healing response , leaving behind fibrotic tissue due to irregular collagen formation . There are different types of scar including atrophic , hypertrophic, contracture and keloid scars. Available scar revision therapies depend on the type of scar , and range from topical creams for mild scarring , to grafting in the case of large , traumatic scars . Laser scar revision is an effective method for treating a wide rang of scars that improves skin texture and pigment as well as functional aspects . Objective:To evaluate the results of using fractional CO2 laser in the treatment of surgical and traumatic scars. Patients and Methods: A prospective study in which 35 patients with surgical and traumatic scars situated on different areas of the face , and of different types and size , they were 10(28.6%) males and 25(71.4%) females , their ages ranged from (8-60) years, with a mean age (27.2±8) years . The study was conducted in a private clinic in Kalar City , Al-Sulaymania Province for the period from January 2015 to December 2016 . They were examined and assessed regarding the type of scars , size , duration and previous therapy as well as the reasons behind the consultation of doctor . The patients were divided into three groups according to the type of scar , atrophic , hypertrophic and keloid . All patients were treated by fractional CO2 laser , different number of sessions were done at monthly interval after topical application of emila for induction of anesthesia , for 45 minutes . The response to treatment was classified into three degrees , good, moderate and poor response . Results: The patients were divided into three groups according to the type of scar , they were atrophic scar 30(85.7%) patients , hypertrophic 3(8.6%) patients and keloid 2(5.7%) patients . The response to treatment in those with atrophic scars was good in 25(71.4%) patients and moderate in 5(14.3%) , while all patients with hypertrophic scars shows moderate response and those with keloid shows poor response. The sex and age had no significant effects on the response to treatment . Some patients 8(11.4%) developed hyperpigmentation at the site of therapy , specially those with darker skin (type-4) . Conclusion: It was concluded that fractional CO2 laser was a good therapeutic selection for the treatment of atrophic surgical and traumatic scars specially in those with white skin complexion .